Regional Brain Oxygen Saturation: There is also Life Beyond the Brain - J.L., Guerrero O.; A., Ramirez Fernandez (Current Pharmaceutical Design, 2022)
Some procedures, such as cardiovascular surgery, may compromise brain perfusion and require careful management to preserve the integrity of the central nervous system. In this setting, regional cerebral oxygen saturation [rSO2] emerges as an alternative, minimally invasive, monitoring system. The mechanism by which regional oxygen is measured is based on the refraction and absorption of a signal with a specific wavelength. Diagnostic and therapeutic algorithms for these settings would allow for a more rational use of goal-directed therapies that reduce morbidity and mortality in these patients.
Keywords: Regional oxygen saturation